PERAN SASTRA DALAM PENDIDIKAN ISLAM - Aziz, Abd (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2023)
This paper describes the urgency of literary works as an important learning material in Islamic boarding schools. This condition can be seen in the story learning method which can shape character through appreciation of every side of life so that people can learn to imitate these characters when they are good, and also not to repeat bad events in the story. In this case, literary works can become learning media and methods, even learning strategies and insights in looking at things with a new paradigm. This paper concludes that reading Islamic literature more often can form a broad perspective for its readers, so that they can better appreciate the greatness of God.